Influence of microclimate and geomorphological factors on alpine vegetation in the Western Swiss Alps. Issue 15 (23rd October 2019) - Giaccone, Elisa; Luoto, Miska; Vittoz, Pascal; Guisan, Antoine; Mariéthoz, Grégoire; Lambiel, Christophe
Abstract: Among the numerous environmental factors affecting plant communities in alpine ecosystems, the influence of geomorphic processes and landforms has been minimally investigated. Subjected to persistent climate warming, it is vital to understand how these factors affect vegetation properties. Here, we studied 72 vegetation plots across three sites located in the Western Swiss Alps, characterized by high geomorphological variability and plant diversity. For each plot, vascular plant species were inventoried and ground surface temperature, soil moisture, topographic variables, earth surface processes (ESPs) and landform morphodynamics were assessed. The relationships between plant communities and environmental variables were analysed using non‐metric multi‐dimensional scaling (NMDS) and multivariate regression techniques (generalized linear model, GLM, and generalized additive model, GAM). Landform morphodynamics, growing degree days (sum of degree days above 5°C) and mean ground surface temperature were the most important explanatory variables of plant community composition. Furthermore, the regression models for species cover and species richness were significantly improved by adding a morphodynamics variable. This study provides complementary support that landform morphodynamics is a key factor, combined with growing degree days, to explain alpine plant distribution and community composition. © 2019 John Wiley & Sons, Ltd. © 2019 John Wiley & Sons, Ltd. Abstract : In the western Swiss Alps we investigated the influence of geomorphic processes and landforms on alpine plant communities. Vascular plant species were inventoried and ground surface temperature, soil moisture, topographic variables, earth surface processes and landform morphodynamics were assessed. This study provides complementary knowledge indicating that landform morphodynamics, combined with growing degree days, is a key factor to explain alpine plant distribution and community composition.